SPIRITUAL EDUCATION OF EARLY CHILDREN FROM THE AL-QUR'AN PERSPECTIVE - Bani Halim, Junaiji Abd. Halim (UIN Mataram, 2023)
Abstract: Early childhood spiritual education in the perspective of the Qur'an is an educational process that emphasizes growing the spiritual potential of children that they carry from birth through the cultivation of religious spiritual values which include Aqidah, Iman, Islam and Ihsan which are applied directly to early childhood, as an effort to revive and develop the potential of children's nature that is carried from birth. Spiritual education will not grow by itself without guidance sourced from divine revelation. Spirituality that is taught without involving the guidance of divine revelation will be limited to logical views only. Then this spirituality will be dry and far from the guidance of the Creator. So spiritual education must be taught and developed through spiritual education sourced from religious teachings, because spirituality is closely related to divinity. To revive the spirituality of early childhood can only be done through the cultivation of religious spiritual values such as teaching faith, Islam and Judaism, because these three sources are known as religious foundations. Thus this research differs from the view that: to revive spirituality does not require the role of religion. Keywords: Spiritual Education, Early Childhood, Qur'an.